Performa Strategis Rumah Bersalin Cuma-Cuma (RBC) Sinergi Foundation dalam Membangun Habitus Kesehatan Kaum Duafa - Budiman Pohan; Hadiyanto Abdul Rachim; Gigin Ginanjar Kamil Basar (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2020)
This study aims to describe the strategic performance of the Rumah Bersalin Cuma-Cuma (RBC) Sinergi Foundation Bandung in building a habitus of health for the dhuafa. This research is motivated by the existence of RBC-SF as a primary clinic that facilitates women of the dhuafa as members with free health and empowerment services sourced from zakat, infaq, alms, and productive waqf funds. The research method used a qualitative approach and focused on case studies, while informants were selected purposively. Data are collected in parallel through observation, interviews, and documentation. Then the data is processed through the stages of collection, reduction, visualization, verification, and conclusion. The results showed that the strategic performance of RBC-SF includes: 1) strengthening the biological capacity of mothers and children; 2) participation and delivery administration support; 3) regular education through recitation and seminars; 4) capacity building of skills through training; and 5) legitimacy and appreciation for graduation and awareness of members to continue participating in the RBC-SF program. The strategic implications of developing habitus of health, include: 1) building social networks and entrepreneurial skills; 2) the importance of involving spiritual awareness in living life; 3) healthy living culture which is passed down genealogically; and 4) the importance of women's participation in habituating family health.